Exploring the mental strength of Myasthenia Gravis patients: A statistical and language learning model approach for understanding coping and adaptation - Conte, Luana; Lupo, Roberto; Lezzi, Pierluigi; Panzanaro, Ludovica; Rizzo, Francesco; Fasano, Antonio; Lezzi, Tania; Rubbi, Ivan; Vitale, Elsa; Artioli, Giovanna; Cascio, Donato; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Myasthenia Gravis (MG) is a chronic autoimmune neuromuscular disorder characterized by muscle weakness and fatigue, significantly affecting physical abilities, emotional well-being, and social interactions. Coping strategies play a crucial role in disease management, yet there is limited knowledge on how MG patients adapt to their condition. This study aims to explore the coping mechanisms employed by individuals with MG to identify patterns that may inform targeted interventions for improving their overall well-being. Methods: We conducted an anonymous online survey from January to April 2023, recruiting MG patients through social media groups. The survey included socio-demographic questions and the validated Coping Orientation to Problems Experienced (COPE-NVI-25) questionnaire to assess coping strategies. Additionally, two open-ended questions allowed participants to express their concerns and suggestions regarding disease management. We analyzed structured responses using statistical methods, while open-ended responses were processed through a Large Language Model (LLM)-assisted sentiment analysis and clustering technique. Results: A total of 215 MG patients participated. Most respondents lacked prior knowledge of MG before diagnosis and reported dissatisfaction with available health education. COPE-NVI-25 results showed that Positive Attitude was the most frequently adopted strategy, while Avoidance Strategies and Transcendent Orientation were the least used. LLM-assisted analysis of open-ended responses highlighted patients’ concerns regarding inadequate communication with healthcare providers, lack of guidance on coping strategies, and the desire for more patient-centered care. Conclusions: This study provides novel insights into the coping strategies of MG patients, highlighting the need for improved education and tailored interventions